Effects of computer-generated patterns with different temporal and spatial frequencies on choroidal thickness, retinal dopamine and candidate genes in chickens wearing lenses - Liu, Hong; Schaeffel, Frank; Feldkaemper, Marita Pauline (Frontiers in Medicine, 2024)
Version July 19October 17, 2024 vitreal level of dopamine metabolites. Retinal EGR-1 mRNA level was positively correlated with choroidal thickness. Retinal OPN4 melanopsin mRNA was increased by 10 Hz-ON stimulation and choroidal BMPR1A mRNA increased with 10 Hz-OFF stimulation. Averaged overOn average all experiments, early choroidal thinning did not predict the amount of negative lens-induced eye growth changes after 7 days, whereas later ChT changes showed a weak association.Negative lenses caused long-lasting choroidal thinning, with some recovery during lens wear, especially after stimulation with 10 Hz.The dynamic stimuli modulated choroidal thinning but effects were small.There was little difference between ON and OFF stimulation, perhaps because the checkerboard patterns were too coarse. 10 Hz cycle frequency increased dopamine release. Less dopamine was correlated with thinner choroids. Result do not exclude a predictive value of choroidal thickeningChT for future refractive development since we almost exclusively tested choroidal thinning effects.